Doggy day care - Stern, A. J.; Mulryan, Doreen (New York : Grosset & Dunlap, 2010)
Frannie must rethink her dream of becoming a veterinarian after she and Elliott, her future assistant, cause chaos by letting her Aunt Magoo's dog, Bark, loose in a veterinarian's waiting room.
Includes an excerpt from Check, please (p. 126-128).
Keywords: Pet sitting; Behavior; Dogs; Cats; Veterinarians; Family life